Õhuvaatlusvõrgustik Eesti õhukaitses [The aerial observation network in Estonian air defence] - Raudvassar, Mika (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
Mankind has been fighting since the beginning of time: first on land, then on sea, and since 1794 in the air as well. Different kinds of aircraft have nasty characteristics compared to the weapons used on land or sea – the speed and agility of the former being independent from the roads and other infrastructure.Since World War I it has been mentioned that aircrafts are extremely dangerous for the civilian population. For example, different organisations were formed for aerial observation matters in order to provide self-defence. After the establishment of Air Defence, the third service arm in the Estonian Defence Forces, in 1930, such a network was created here. It involved six different organisations and three of them were clearly civilian. The network developed in the 1930s was put into action during the Soviet–Finnish Winter War as the Soviet bases were set up in Estonia after the Bases Agreement. It can be said that when World War II started, Estonian Air Defence was totally unprepared for it due the lack of resources in the field of active air defence.